Efficiency of Isolated and Associated Herbicides to Control Glyphosate-Resistant Sourgrass - CASSOL,M. (2019)
ABSTRACT: Sourgrass is one of the weeds of great economic importance in Brazil due to its difficulty of control and conditions that allow its emergence and development throughout the year. Thus, this study aimed to evaluate the effectiveness of clethodim and haloxyfop applied alone or mixed with glyphosate and other herbicides to control glyphosate-resistant sourgrass at different stages of development. For this, three experiments were conducted in the field: in experiment 1, the herbicides were applied in sourgrass plants with 6 to 8 tillers; and in experiments 2 and 3, when plants were at full flowering, with up to 18 tillers. After treatment application, visual evaluations were performed at 14, 21, 28, 35, 42, 49, and 56 days after application (DAA) in experiment 1 and at 7, 14, 21, 28, and 35 DAA in experiments 2 and 3. Also in experiment 3, the shoot of remaining plants was collected in the last control evaluation to measure the dry matter. In experiment 1, the treatment glyphosate + clethodim presented a satisfactory control close to 90%, but after 35 DAA, sourgrass plants started showing significant resprouts, decreasing the control. In experiments 2 and 3, treatments showed no control above 90% and the herbicides clethodim and haloxyfop had similar final control when in mixture with glyphosate. Therefore, the isolated herbicide application at the tested doses was not sufficient for efficient control of sourgrass at more advanced stages of development.